Pengendalian Kualitas Kertas Dengan Menggunakan Statistical Process Control di Paper Machine 3 - Vera Devani; Fitri Wahyuni (Jurnal Ilmiah Teknik Industri, 2016)
Purpose of this research is to determine types and causes of defects commonly found in Paper Machine 3 by using statistical process control (SPC) method.  Statistical process control (SPC) is a technique for solving problems and is used to monitor, control, analyze, manage and improve products and processes using statistical methods.  Based on Pareto Diagrams, wavy defect is found as the most frequent defect, which is 81.7%.  Human factor, meanwhile, is found as the main cause of defect, primarily due to lack of understanding on machinery and lack of training both leading to errors in data input.